Efektivitas Handout pada Pembelajaran Kimia dalam Meningkatkan Prestasi Siswa: Review - Ayu, Venanda Risma Kurnia; Rinaningsih, Rinaningsih (Chemistry Education Review (CER), 2021)
This study aims to analyze the effectiveness of handouts as an alternative to learning chemistry in improving student achievement. The method used in this article is a meta-analysis of several pieces of literature relevant to the topic and research objectives. The handout was identified as having an optimal level of practicality, and was considered adequate for students because it made it easier for students in the learning process. The teacher's role in this method is more to strengthen the material by providing an understanding of the inappropriate material delivered by the group. The teacher and the students concluded the results obtained, and an assessment was carried out to determine the level of achievement of the cycle I. In the next stage in cycle II, the group assistants were expected to understand other students so that interactions between students were identified as contributing to the second cycle assessment results. The result is an increase in student achievement in both cognitive and affective aspects. The cognitive aspects previously at the level of achievement of 42.11% increased to 63.16% exceeding 60%. Meanwhile, the affective   aspect increased from 70.24% to 74.47%. The combination of discussion methods and handouts, and also videos as learning media can improve student learning outcomes or student achievement more effectively.